Stabilizing the national banking system through digital financial inclusion, creative innovations, and green finance in low-financially developed economies - Giang Thi Huong Vuong; Walid Barky; Manh Huu Nguyen (Journal of Open Innovation: Technology, Market and Complexity)
This paper investigates the effect of digital financial inclusion, creative innovations, and green finance on the stability of the national banking system in twenty-nine low-financially developed economies spanning the period 2011–2021. We demonstrate that digital financial inclusion promotion reduces banking system stability in low-financially developed economies. Additionally, creative innovations mitigate the adverse impact of digital financial inclusion on banking stability in low-financially developed economies. These findings are consistent using diverse econometric techniques. In highly developed economies, digital financial inclusion enhances national banking stability. Furthermore, green finance amplifies the positive relationship between digital financial inclusion and banking stability in high-financially developed economies. Our work sheds light on the crucial roles of digital financial inclusion, creative innovations, and green finance in the stability of national banking systems in low-financially developed economies and provides interesting comparison findings. Furthermore, this study offers recommendations for related governments and policymakers in low-financially developed economies to prioritize creative innovation to promote digital financial inclusion and stabilize the national banking system. For high-financially developed economies, encouraging green finance implementation is crucial and contributes to the banking system's stability.